The Role of School Field Introduction Program Students in the Learning Process at SMK Negeri 4 Makassar - Meisya Luna Assyura; Haedar Akib; Nasaruddin Hasyim (Journal of Educational Development and Learning (JEDAL), 2025)
The School Field Introduction Program (PLP) is a form of teaching practice experience for education students to develop pedagogical, professional, social, and personality competencies. This study aims to analyze the role of PLP students in the learning process at SMK Negeri 4 Makassar and its impact on the effectiveness of teaching and learning activities. The approach and type of research used are qualitative research approaches and descriptive research types. The informants in this study were the head of the MPLB (Office Management and Business Services) department and two supervising teachers. The methods used in this study were observation, interviews with supervising teachers and the head of the department, and analysis of learning documents. The data analysis techniques employed were data condensation, data presentation, and drawing conclusions. Based on the study's results, it was demonstrated that PLP students played a role in assisting with teaching planning, including compiling lesson plans, determining appropriate learning strategies, and preparing media and teaching materials that support the learning process in the classroom. (2) Learning Management, such as organizing the course of teaching and learning activities, creating a conducive classroom atmosphere, and helping teachers handle class dynamics during the learning process. (3) evaluation of student learning outcomes through the preparation of teaching materials, arrangement of teaching and learning activities in the classroom, and implementation of learning outcome assessments to determine the achievement of student competencies. (4) utilization of learning technology, such as using Google Classroom for class management, Canva to create interesting learning media, and Quizzes and Google Forms as interactive and efficient learning evaluation tools to increase student engagement. However, several challenges are faced, including difficulties in adapting learning methods to student characteristics and the need for additional support from mentor teachers. Overall, the presence of PLP students makes a positive contribution to improving the quality of learning at SMK Negeri 4 Makassar.